2018
DOI: 10.1042/bsr20180713
|View full text |Cite
|
Sign up to set email alerts
|

Complement is a rat natural resistance factor to amoebic liver infection

Abstract: Amoebiasis is a parasitic disease caused by Entamoeba histolytica. This illness is prevalent in poor countries causing 100,000 deaths worldwide. Knowledge of the natural resistance mechanisms of rats to amoebic liver abscess (ALA) development may help to discover new pathogenic factors and to design novel therapeutic strategies against amoebiasis. In this work, histologic analyses suggested that the complement system may play a central role in rat natural resistance to ALA. E. histolytica trophozoites disappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Amoebic cysteine proteinases play a role in cleavage of complement components (5052). Amoebae are also made temporarily resistant to complement lysis through treatment with increasing doses of heat-inactivated human serum, though the mechanism remains unclear (37, 53), and it was recently found that amoebae do not develop resistance to serum from rats by this method (54). As the percentage of amoebae lysed after exposure to human serum in our assays never reached 100%, even under conditions where amoebae were incubated alone, it is likely that multiple factors contribute to complement resistance in E.…”
Section: Discussionmentioning
confidence: 99%
“…Amoebic cysteine proteinases play a role in cleavage of complement components (5052). Amoebae are also made temporarily resistant to complement lysis through treatment with increasing doses of heat-inactivated human serum, though the mechanism remains unclear (37, 53), and it was recently found that amoebae do not develop resistance to serum from rats by this method (54). As the percentage of amoebae lysed after exposure to human serum in our assays never reached 100%, even under conditions where amoebae were incubated alone, it is likely that multiple factors contribute to complement resistance in E.…”
Section: Discussionmentioning
confidence: 99%
“…The potent amoebicidal activity of complement in Wistar rats is responsible for parasite elimination before 6 h [5]. In contrast, the amoebicidal activity of complement in Balb/c mouse is not involved in the parasite clearance from liver since hypocomplementemia did not modify the survival time of the parasite (72 h).…”
Section: Discussionmentioning
confidence: 99%
“…Innate immunity may play an important role in such resistance since in most of them the parasite is cleared before the specific immune response. Recently, it was determined that serum complement of Wistar rats is lethal for the parasite and is involved in their resistance to EALA [5]. Furthermore, Balb/c mice have been used to study the EALA development; however, contrasting results have been published showing early as well as late clearance of the parasites (from 1 to 7 days) [6–10].…”
Section: Introductionmentioning
confidence: 99%
“…Amoebic cysteine proteinases play a role in cleavage of complement components [50–52]. It has also been reported that amoebae are made temporarily resistant to complement lysis through treatment with increasing doses of heat-inactivated human serum, though the mechanism remains unclear [37,53], and it was recently found that amoebae do not develop resistance to serum from rats by this method [54]. As the percentage of amoebae lysed after exposure to human serum in our assays never reached 100%, even in conditions where amoebae were incubated alone, it is likely that multiple factors contribute to complement resistance in E. histolytica.…”
Section: Discussionmentioning
confidence: 99%